Analysis of Patients' Online Reviews of Orthopaedic Surgeons. (18th October 2022) - Berns, Ellis M.; Reid, Daniel B. C.; Anderson, George M.; Alsoof, Daniel; Shapiro, Benjamin; Zhang, Andrew S.; Daniels, Alan H.
Abstract : Introduction: Physician rating websites (PRWs) are an increasingly popular interface between patient and surgeon. Despite the growing popularity of PRWs, little guidance exists for orthopaedic surgeons regarding online reviews. We analyzed online ratings and comments to provide a better understanding of patients' values and expectations so that surgeons can tailor their practice accordingly to enhance their clinical care and online reputation. Methods: Three common PRWs (Vitals, HealthGrades, and RateMDs) were queried from January 1, 2006, to May 18, 2020. Publicly available ratings, both quantitative (1 to 5 stars) and qualitative (free text comments), were collected. Comments were qualitatively tabulated as having positive or negative assessments for categories including outcome, personality, staff, surgical skill, visit time, bedside manner, wait time, diagnosis, knowledge, treatment, and advanced practice providers and analyzed using chi square goodness of fit. Quantitative comparisons of star ratings were made across surgeon years in practice, sex, practice setting, and PRW and compared using chi square independence testing. Results: In total, 81% of patient comments were found to have a positive assessment. Comments regarding outcome ( P < 0.001), staff ( P = 0.001), surgical skill ( P < 0.001), or knowledge ( P = 0.001) were more likely to be positive. Reviews regarding bedside manner ( P < 0.001), wait time ( P < 0.001), diagnosis ( P < 0.001), treatment ( P < 0.001), or advanced practice providers ( P < 0.001) were more likely to be negative. Surgeon sex was not associated with a difference in quantitative ratings ( P = 0.131), unlike practice setting ( P < 0.001) and PRW ( P < 0.001). Discussion: PRWs are a growing interface between surgeon and patient with a considerable effect on surgeon marketability. This study reveals a statistical association between certain patient-centered medical practices and positive patient reviews. This emphasizes the importance of ensuring that high standards are maintained throughout a physician's practice of maintaining a constant awareness of the fundamentals for effective patient care and of taking care to curate a physician's online presence.